2016
DOI: 10.1016/j.rbmo.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrauterine HCG injection on IVF outcome: a systematic review and meta-analysis

Abstract: In this systematic review and meta-analysis, the effect of intrauterine HCG infusion before embryo transfer on IVF outcomes (live birth rate, clinical pregnancy rate and spontaneous aboretion rate) was investigated. Searches were conducted on MEDLINE, EMBASE and The Cochrane Library. Randomized studies in women undergoing IVF and intracytoplasmic sperm injection comparing intrauterine HCG administration at embryo transfer compared with no intrauterine HCG were eligible for inclusion. Eight randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…However, after analyzing eight RCTs, Osman et al [26] concluded that the current evidence did not support the use of intrauterine hCG injection before ET. A total of 3087 women undergoing IVF/ICSI (intrauterine hCG group: n  = 1614; control group: n  = 1473) were enrolled.…”
Section: Discussionmentioning
confidence: 94%
“…However, after analyzing eight RCTs, Osman et al [26] concluded that the current evidence did not support the use of intrauterine hCG injection before ET. A total of 3087 women undergoing IVF/ICSI (intrauterine hCG group: n  = 1614; control group: n  = 1473) were enrolled.…”
Section: Discussionmentioning
confidence: 94%
“…More importantly, this finding was independent of blastocyst quality and of HCG administration timing (either two days or immediately prior to embryo transfer). The size of that study was large enough for a second meta-analysis to be performed and published later on by Osman et al [44]. This included eight studies with 3087 participants, randomized as a study (HCG) group ( n = 1614) and a control group ( n = 1473).…”
Section: Hcg and Clinical Applications In Assisted Reproduction Tementioning
confidence: 99%
“…Unfortunately, the administration of these biologics has not been developed based on the assessment of endometrial receptivity using specific biomarkers. 14,19 In this review, IUI-hCG will be critically evaluated by discussing the possible immune modulatory effect of hCG, analyzing the differences in experimental designs, outcomes, and limitations of previous studies, and providing future directions for this treatment. Increasing number of clinical trials to investigate the clinical efficacy of IUI-hCG before embryo transfer has been reported since 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of therapeutics, the main objective has been to develop clinical interventions to improve endometrial receptivity by introducing factors, including intrauterine infusion of chorionic gonadotropin (IUI-hCG), 14 granulocyte colony-stimulating factor (G-CSF), 15 peripheral blood mononuclear cells (PBMC), 16 and blood platelet, 17 in the uterus that will act directly in the cellular components of the endometrium. Unfortunately, the administration of these biologics has not been developed based on the assessment of endometrial receptivity using specific biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation